1964
DOI: 10.1136/gut.5.4.342
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of secretin and cholecystokinin on Heidenhain pouch responses to gastrin extract and histamine

Abstract: MATERIALS AND METHODSFive dogs with Heidenhain type denervated fundic pouches created more than six months previously were studied.Secretin and cholecystokinin, prepared by the method of Jorpes and Mutt (1959), were obtained from Vitrum (Stockholm). Gastrin extract was prepared from hog antral mucosa by a modification of the method of Gregory and Tracy (1961) previously described (Gillespie and Grossman, 1963); doses are expressed as the equivalent weight in grams of wet antral mucosa.The dogs were deprived of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
1

Year Published

1969
1969
1989
1989

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(23 citation statements)
references
References 10 publications
2
20
1
Order By: Relevance
“…Secretin has been shown to inhibit acid secretion stimulated by food and antral irrigation ( l ) , duodenal distension ( 2 ) , intestinal stimulation (3), and exogenous gastrin (4). Although pure secretin is a potent inhibitor of gastrin-stimulated secretion in the dog ( 5 ) , it has little effect on gastric acid secretion in the cat (6).…”
Section: Effect Of Secretin and Cholecystokinin On Thementioning
confidence: 99%
“…Secretin has been shown to inhibit acid secretion stimulated by food and antral irrigation ( l ) , duodenal distension ( 2 ) , intestinal stimulation (3), and exogenous gastrin (4). Although pure secretin is a potent inhibitor of gastrin-stimulated secretion in the dog ( 5 ) , it has little effect on gastric acid secretion in the cat (6).…”
Section: Effect Of Secretin and Cholecystokinin On Thementioning
confidence: 99%
“…At present we have no explanation for these species differences. In addition to the data obtained with metiamide and propranolol, it is well known that both secretin and glucagon markedly inhibit the gastric secretion induced by gastrin but not that induced by histamine (14)(15)(16). We have already reported that atropine sulfate markedly inhibited the methacholine or tetragastrin stimulated gastric secretion but exerted less influence on histamine stimulated secretion in anesthetized dogs (17).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that cholecystokinin peptides inhibit parietal cell activity in vivo (Gillespie & Grossman, 1964;Brooks, Agosti, Bertaccini & Grossman, 1970;Sj6din, 1972;Holstein, 1982) and in vitro (Schepp, Ruoff & Maslinski, 1983;Bengtsson & Nilsson, 1989) (Davison & Najafi-Farashah, 1987), showing that the CCK antagonist dibutyryl cyclic GMP interferes with vagal inhibitory impulses possibly mediated by a CCK peptide.…”
Section: Discussionmentioning
confidence: 99%